Co2 Emission And Carbon Capture For Coal Fired Power Plants In Malaysia And Indonesia. - Martunus, Martunus; Othman, M.R.; Zakaria, R.; Fernando, W.J.N. (2008)
Coal consumption in Malaysia and Indonesia is growing at the rate of 9.7 and 4.7% per year since 2002, respectively. The increase in coal utilization usually tallies fairly well with the increase in CO2 emission. The present study attempts at predicting the emissions of CO2 from coal fired power plants from 2005 until 2020.